Reading as culture: promoting! sustaining!! inspiring!!! (2015)
Many librarians in developing countries complain of poor funding and lack of current books as factors that elicit low reading interests among young people. This interest cannot be stimulated inhere there is no motivating factor and the professionals are seemingly passive. This paper takes a look at reading as culture and explores how reading can be promoted, sustained and inspired by all in the bid for lifelong education. A model for reading advocacy by librarians, teachers, parents, health caregivers and educators generally is proposed. Suggestions are made on how librarians can, through partnership with different stakeholders; publishers, illustrators, reading tutors and classroom teachers get people especially young ones to love the art of reading, and for more community effort, partnerships and advocacy for reading programmes that will help bring out the creativity in people and build a sustainable reading culture.